Heart failure with preserved ejection fraction according to the HFA‐PEFF score in COVID‐19 patients: clinical correlates and echocardiographic findings. (12th July 2021) - Hadzibegovic, Sara; Lena, Alessia; Churchill, Timothy W.; Ho, Jennifer E.; Potthoff, Sophia; Denecke, Corinna; Rösnick, Lukas; Heim, Katrin Moira; Kleinschmidt, Malte; Sander, Leif Erik; Witzenrath, Martin; Suttorp, Norbert; et al.
Abstract: Aims: Viral‐induced cardiac inflammation can induce heart failure with preserved ejection fraction (HFpEF)‐like syndromes. COVID‐19 can lead to myocardial damage and vascular injury. We hypothesised that COVID‐19 patients frequently develop a HFpEF‐like syndrome, and designed this study to explore this. Methods and results: Cardiac function was assessed in 64 consecutive, hospitalized, and clinically stable COVID‐19 patients from April–November 2020 with left ventricular ejection fraction (LVEF) ≥50% (age 56 ± 19 years, females: 31%, severe COVID‐19 disease: 69%). To investigate likelihood of HFpEF presence, we used the HFA‐PEFF score. A low (0–1 points), intermediate (2–4 points), and high (5–6 points) HFA‐PEFF score was observed in 42%, 33%, and 25% of patients, respectively. In comparison, 64 subjects of similar age, sex, and comorbidity status without COVID‐19 showed these scores in 30%, 66%, and 4%, respectively (between groups: P  = 0.0002). High HFA‐PEFF scores were more frequent in COVID‐19 patients than controls (25% vs. 4%, P  = 0.001). In COVID‐19 patients, the HFA‐PEFF score significantly correlated with age, estimated glomerular filtration rate, high‐sensitivity troponin T (hsTnT), haemoglobin, QTc interval, LVEF, mitral E/A ratio, and H2 FPEF score (all P  < 0.05). In multivariate, ordinal regression analyses, higher age and hsTnT were significant predictors of increased HFA‐PEFF scores. Patients with myocardial injury (hsTnT ≥14 ng/L: 31%) vs. patients without myocardial injury, showed higher HFA‐PEFF scores [median 5 (interquartile range 3–6) vs. 1 (0–3), P  < 0.001] and more often showed left ventricular diastolic dysfunction (75% vs. 27%, P  < 0.001). Conclusion: Hospitalized COVID‐19 patients frequently show high likelihood of presence of HFpEF that is associated with cardiac structural and functional alterations, and myocardial injury. Detailed cardiac assessments including echocardiographic determination of left ventricular diastolic function and biomarkers should become routine in the care of hospitalized COVID‐19 patients.